Enhancing Critical Thinking Skills in Mathematics Education: Integrating Problem-Based Learning in Seconday Schools - Baso Intang Sappaile; Sayida Khoiratun Nisak; Ahmad Afandi; Sofiyatul Anshoriyah; Mardiati Mardiati (PT Inovasi Pratama Internasional, 2024)
Mathematics has an instrumental function in enhancing the quality of Indonesian citizens. However, as science and technology progress and the digital age intensifies, it has become imperative to modify the mathematical learning paradigm to align it with the demands of the 21st century. The research objectives were to ascertain the following: The study sought to answer three research questions(1) the difference in the improvement of mathematical critical thinking ability of students who are given problem-based learning with students who are given direct learning; (2) the interaction of learning with initial mathematics ability on the improvement of students' mathematical critical thinking ability; (3) the difference in the improvement of learning independence of students who are given problem-based learning with students who are given direct learning. The findings of the study can be summarized as follows: (1) students who received problem-based learning exhibited a greater improvement in their mathematical critical thinking abilities than those who received direct learning; (2) there was no interaction between learning and initial mathematical ability on the improvement of mathematical critical thinking abilities; (3) students who received problem-based learning demonstrated a greater improvement in their learning independence than those who received direct learning.